Answer:
Four
Explanation:
We have the expression
.
Now, four different students have applied different properties to rewrite the expression above.
1. Mitul used commutative property i.e. ab = ba
So,
=
.
2. Stacy used associative property i.e. a(bc) = (ab)c
Then,
=
![-5[((-2)/(7)* (4)/(11))(-9)]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hhqvs1yj912td5tzk17okccpgh2bk0yuz1.png)
3. Tom used associative property followed by commutative property
Thus,
=
=
![-5[((4)/(11)* (-2)/(7))(-9)]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wu84vl7mqw7kcmz4dvcuk2tvma9ulivsg3.png)
4. Walt used commutative property followed by associative property
So,
=
=
=
.
Hence, we see that all the four students have rewritten the expressions equivalent to the original expression.